Difficulties in Pronouncing English Vowel and Consonant by English Language Education Undergraduate Students at UINSU - Muhammad Arkan Syafiq; Muhammad Hafiz (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research investigates the challenges encountered by undergraduate students majoring in English Language Education at UINSU (State Islamic University of North Sumatra) when pronouncing English vowels and consonants. A descriptive qualitative research method was employed, involving 25 students from the fourth semester of the English Language Education program. The results revealed several difficulties faced by the students, including difficulty pronouncing vowel and consonant sounds that are not present in their mother tongue, challenges in matching the sound of English words with their written form, struggles in determining the correct sound to use in different words or sentences, interference of the mother tongue on the pronunciation of English vowels and consonants, and difficulties in accurately pronouncing English vowels and consonants due to inconsistencies in pronunciation. These findings highlight the need for targeted instruction and practice to address these challenges and enhance students' pronunciation skills in English language learning.